Bioproducts from seaweeds: a review with special focus on the Iberian Peninsula - Cardoso, Susana M. (2014)
Seaweeds, i.e. macroalgae that occupy the littoral zone, are a great source of compounds with diverse applications; their types and content greatly determine the potential applications and commercial values. Algal polysaccharides, namely the hydrocolloids: agar, alginate and carrageenan, as well as other non-jellifying polysaccharides and oligosaccharides, are valuable bioproducts. Likewise, pigments, proteins, amino acids and phenolic compounds are also important, exploitable compounds. For the longest time the dominant market for macroalgae has been the food industry. More recently, several other industries have increased their interest in algal-derived products, e.g. cosmetics, pharmaceuticals and more recently, as a source of feedstock for biorefinery applications. This manuscript reviews the chemical composition of dominant macroalgae, as well as their potential added-value products and applications. Particular attention is devoted to the macroalgal species from the Iberian Peninsula. This is located in the Southwest of Europe and is influenced by the distinct climates of the Mediterranean Sea and the Atlantic Ocean, representing a rich spot of marine floral biodiversity.